Tadeusz Kundzicz – professor of higher applied mathematics at the Vilnius university in the 18th century - Gečiauskas, Evaldas (Lietuvos matematikos rinkinys, 2005)
Tadeusz Kundzicz (1747–1829) was a professor of higher applied mathematics at the Vilnius university in the period from 1780 until 1802 and he tought mechanics by the tractate of J.X. de la Caille containing statics, dynamics, equilibrium, centre of gravity, machines and complementary subjects by Heron, Torriceli, Borellus, Mariote, Castel, Varignon, Helidor, and military architecture by de Pagan, Blondelius and Vauban.